Mesenchymal Stem Cell Enhances the Function of MDSCs in Experimental Sjögren Syndrome - Tian, Jie; Hong, Yue; Zhu, Qiugang; Zhou, Huimin; Zhang, Yidan; Shen, Ziwei; Guo, Hongye; Zhang, Yue; Ai, Xiangyan; Zhao, Futao; Rui, Ke; Xu, Huaxi; et al. (Frontiers in Immunology, 2020)
Primary Sjögren’s syndrome (pSS) is a progressive systemic autoimmune disease characterized by lymphocytic infiltrates in exocrine glands, leading to the injury of salivary and lachrymal glands. Mesenchymal stem cells (MSCs) have been demonstrated to exert great potential in the treatment of various autoimmune diseases. Although MSCs have provide an effective therapeutic approach for SS treatment, the underlying mechanisms are still elusive. Our previous study has shown the reduced suppressive capacity of myeloid-derived suppressor cells (MDSCs) advanced the progression of experimental Sjögren’s syndrome (ESS). In this study, we found that BM-MSCs significantly enhanced the suppressive function of MDSCs with high levels of Arginase and NO, decreased the levels of CD40, CD80, CD86 and MHC- II expression on MDSCs, thus attenuating the disease progression in ESS mice. Furthermore, the enhanced suppressive function of MDSCs was mediated by BM-MSC-secreted TGF-β, and the therapeutic effect of BM-MSCs in inhibiting ESS was almost abolished after silencing TGF-β in BM-MSCs. Taken together, our results demonstrated that BM-MSCs alleviated the ESS progression by up-regulating the immunosuppressive effect of MDSCs through TGF-β/Smad pathway, offering a novel mechanism for MSCs in the treatment of pSS.